Pengaruh Pemberian Kompres Daun Kubis Dingin sebagai Terapi Pendamping bendungan ASI terhadap Skala Pembengkakan dan Intensitas Nyeri Payudara serta Jumlah ASI pada Ibu Postpartum di RSUD Bangil - Damayanti, Ervi; Ariani, Dewi; Agustin, Danik (Journal of Issues in Midwifery)
Breast engorgement is a common problem in early postpartum, causing discomfort to become one of the obstacles in exclusive breastfeeding. Therefore, an effective method is needed to solve this problem. This study aimed to determine the effect of cold cabbage leaf compression on the engorgement scale and breast pain intensity, and the amount of breast milk in postpartum mothers. This study was Quasy Experimental with pre-test post-test with control group design, with 32 samples of postpartum mothers with breast engorgement, divided into two groups (intervention and control), with sampling technique of quota sampling. The data collection used a questionnaire sheet containing Six Point Engorgement Scale, Numeric Ratting Scale/NRS. Analysis of this study using Wilcoxon and Mann-Whitney test. The results showed that the compression of cold cabbage leaves had a significant effect on the decrease of engorgement scale and the intensity of pain, and increase of breastmilk with p-value of 0.000 (Î± <0,05), the control group (hand expression) also had significant influence on engorgementÂ scale and the intensity of pain, and the amount of breastmilk with p-value Î± <0,05. There were significant differences in both groups in reducing engorgement and pain intensity (p-value <0.005), but in increasing the amount of breast milk did not show a significant difference between the two groups (p-value 0.344). The conclusion of this study is cold cabbage leaf compresses can be used as a therapy to reduce the scale of engorgement and the intensity of breast pain in mothers with breast engorgement.